Curious George at the beach - Rey, Margret; Shalleck, Alan J (Boston : Houghton Mifflin, 1988)
Curious George's natural agility gives him an unfair advantage when he joins a volleyball game at the beach, but it also helps him rescue a little boy who almost falls off a pier
Cover title: At the beach
"Adapted from the Curious George film series."
Keywords: Beaches -- Fiction; Monkeys -- Fiction